GW24-e0756 Nicotine exacerbates atherosclerosis by upregulation and activation of CD36 in macrophage. (1st October 2013) - Zhou, Ming-Sheng; Hong, Tao; Wang, Aimei; Li, Weihong; Tian, Runxia; Webster, Keith; Raij, Leopoldo
Abstract : Objectives: CD36, a class B scavenger receptor expressed on macrophages mediates uptake of oxLDL and contributes to foam cell formation, a hallmark of early atherosclerosis. Tobacco smoking is a major risk factor for atherosclerosis. We investigated a role for the CD36 pathway in nicotine-induced activation of macrophages and foam cell formation in vitro and in ApoE -/- mice in vivo . Methods: Human THP1-differentiated macrophages were incubated with or without nicotine, the protein and mRNA expression of CD36 or proinflammatory cytokines TNFa, MCP1, IL6 and CXCL9 were determined by real-time PCR or Western blot, respectively, nicotine-induced production of reactive oxygen species were determined by DCFDA assay and lucigenin chemiluminescence. In some experiments, the macrophages were transfected with CD36 siRNA to knockdown CD36. Macrophage uptake of lipoprotein was determined by using 125 I-oxLDL lipoprotein cellular degradation assay. Foam cell formation was determined by Oil O Red staining. For in vivo experiments, apoE -/- and CD36 -/- /apoE -/- double knockout mice were used and treated with normal mice diet, high fat high cholesterol diet (HF) and HF with nicotine for 15 weeks. CD11b + /Ly-6C hi inflammatory monocyte population in peripheral blood mononuclear cells were determined by fluorescence-activated cell sorting analysis. Atheorgenic lesion area in aorta was determined. Results: Nicotine at "physiological" concentrations (100 nmol/L) found in smokers' serum increased mRNA and protein expression of the B scavenger receptor CD36 by 116 ± 19% without affecting the expression of proinflammatory cytokines. These effects of nicotine were mediated by a common signalling pathway dependent on reactive oxygen species, PKCd phosphorylation and PPARg. Antioxidants as well as non-cholinergic nicotinic blockers prevented nicotine-induced CD36 upregulation. OxLDL increased expression of CD36 and proinflammatory cytokines including TNF- a, MCP-1, IL6, and CXCL9, by 2-4 fold (all p < 0.05); the combination of nicotine with OxLDL increased expression of CD36 and inflammatory cytokines by 3-7 fold (all p < 0.05). siRNA knockdown of CD36 significantly reduced mRNA expression of CD36 and the expression of inflammatory genes. Nicotine dose-dependently increased OxLDL uptake (25%) and intracellular cholesterol accumulation in macrophage, which was prevented by CD36 siRNA. Incubation of macrophages with OxLDL for 72 hours resulted in foam cell formation that was exacerbatedby pre-incubation with nicotine in a CD36-dependent manner. Treatment of ApoE -/- mice with physiological concentrations of nicotine markedly enhanced population of peripheral blood inflammatory monocytes (CD11b + /Ly-6C hi population) and aorta atherosclerotic plaque coverage, effects that were not seen in double knockout ApoE -/- /CD36 -/- mice. Conclusions: Our results show for the first time that physiological levels of nicotine increase the expression of CD36 and downstream atherogenic pathways in macrophages. The results with transgenic double knockout ApoE -/- CD36 -/- mice suggest that macrophahge CD36 is a main signaling pathway in responsible for the pro-inflammatory and pro-atherogenic properties of nicotine. These studies identify nicotine as a critical new cardiovascular risk factor of cigarette smoking and caution against the chronic nicotine delivery programs for smoking cessation.